The Effect of Financial Literacy on Interest in Using Fintech Payments on the Shopee Application - Rahayu Rusli; Jumawan Jasman; Asriany; Muhammad Anugrah Ardhana (Jurnal Economic Resource, 2023)
This study aims to determine the effect of financial literacy on interest in using fintech payment processors on the Shopee application. The population in this study were students of the Management Study Program, Faculty of Business Economics, Muhammadiyah University of Palopo. With a total sample of 87 respondents obtained using the purposive sampling technique. The processed data is the result of distributing questionnaires online using a Google form with a Likert scale. The data analysis method used is simple linear regression analysis, analysis of the coefficient of determination, and the t test. The results of the study support the conclusion that financial literacy has a significant effect on interest in using fintech payments (PayLater) in the Shopee application.